Characterization of small extracellular vesicles from ovarian cancer patients and pre-diagnostic patient samples: Evidence from the Danish blood donor study - Nanna Lond Skov Frisk; Malene Møller Jørgensen; Rikke Bæk; Amila Iriskic Atic; Thorsten Rejkjær Brodersen; Sisse Rye Ostrowski; Margit Hørup Larsen; Dorthe Posselt; Estrid Høgdall; Claus Høgdall; Ole Birger Vesterager Pedersen; Louise Torp Dalgaard (PLoS ONE, 2025)
Aim Ovarian cancer (OC) is the leading cause of gynecological cancer deaths. Current biomarkers of OC are not specific or sensitive enough. Extracellular vesicles (EVs), EV surface proteins and their cargo microRNA (miRNA) show potential as biomarkers. This study aimed to characterize the ability of EVs to identify early OC-biomarkers among blood donors six months before their diagnosis. Methods Study groups of OC patients, benign tumor patients (B), healthy blood donors (Control), and blood donors with incident OC diagnosis within six months of the last blood draw (Pre-diagnostic; PD) were established. Small EVs were enriched from plasma using ultracentrifugation. EVs were characterized by Dynamic Light Scattering (DLS), EV Array, NanoFlow Cytometry, Nanoparticle Tracking Analysis, and Western blots. RNA from EVs was isolated. A discovery study was performed on OC and B patients using the TaqMan Array Human MicroRNA A card. A validation study of 9 specific miRNAs was performed using RT-qPCR. Results With DLS, it was identified that the OC patients’ EVs were more heterogeneous in size compared to the other groups. Western blot identified CD63 and TSG101 in the EV enrichments. EV Array assessed 22 known protein biomarkers. TaqMan MicroRNA Array cards indicated a differential miRNA abundance between OC and B; however, technical replication and validation could not validate this pattern. Conclusion This study has analyzed EVs in OC, B, Control, and PD women. More extensive investigations of EV CD9, CD151, and CD81 in conjunction with other risk factors and well-known biomarkers like CA125 or HE4 should be the main objectives of future research.